PENGEMBANGAN KURIKULUM MENUJU SMK INTERNASIONAL - Sudira, Putu (Prosiding Pendidikan Teknik Boga Busana, 2020)
VET curriculum, teaching and learning should be adaptive to the conditions and needs of the new world of work, anticipative the future skills requirements, needs of learners as the whole person for personal fulfilment and preparation for life. VET curriculum, teaching and learning should be pay attention to the trend of future world of work, globalization, localization, individualization to make people (self-) employable and to be a vehicle of transition for individuals to the world of work. VET leads to (self-) employment and income generation which is expected to contribute to the individuals' and their communities' well-being. VET implies the adoption of a holistic approach to skills development for employability and citizenship by placing emphasis within skills training programs on developing a basic skills, thinking skills, personal qualities, generic work skills, and specific skills to prepare the learner for self-reliance and responsible citizenship. Key word: VET, curriculum, teaching, learning, skill